2006
DOI: 10.4028/www.scientific.net/msf.519-521.771
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Copper Content on the Bendability of Al-Mg-Si Alloy Sheet

Abstract: The effects of the copper content on the bendability of Al-Mg-Si alloy T4 sheets were investigated. The Al-Mg-Si alloys with less than 0.01mass%Cu, 0.4mass%Cu and 0.8mass%Cu were prepared, and the time of solution heat treatment was changed to obtain different dispersion conditions of the second phase particles and to obtain different shear band formation conditions by bending. For the samples with less than 0.01mass%Cu and 0.4mass%Cu, no cracks were observed during the bending. For the sample with 0.8mass%Cu,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 3 publications
1
6
0
Order By: Relevance
“…A likely explanation is that the onset of cracking is due to textureinduced strain localization enhanced by the presence of large intermetallics particles. This explanation is consistent with the usual view that considers cracks to be initiated around large intermetallics particles within shear bands that form while these alloys are subjected to bending (see Introduction) [2,3,[5][6][7]19,21,23,26,36,37]. Neither grain structure nor intermetallic particles being influenced by the cooling rate, this is consistent with present data.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…A likely explanation is that the onset of cracking is due to textureinduced strain localization enhanced by the presence of large intermetallics particles. This explanation is consistent with the usual view that considers cracks to be initiated around large intermetallics particles within shear bands that form while these alloys are subjected to bending (see Introduction) [2,3,[5][6][7]19,21,23,26,36,37]. Neither grain structure nor intermetallic particles being influenced by the cooling rate, this is consistent with present data.…”
Section: Discussionsupporting
confidence: 94%
“…Their presence can be reduced with increased solution treatment time [25] or subsequent cooling rate [4,26]. No clear correlation between bendability and the type and proportion of grain boundary (GB) precipitates is established; some authors consider that these have no effects on bendability [6]. There are data to show that precipitation during natural (room-temperature) ageing of T4 alloys has an influence on bendability, causing it to decrease during storage [19,22].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…In this case it is considered that the bendability of aluminium alloy sheets is directly governed by the combined effect of micro-voids formation around large secondphase particles, strain localization and propagation of macroscopic shear bands [10][11][12]. Lievers et al [13] confirmed that the shear bands and void damage development play co-operative role in promoting ductile fracture at the outer free surface during bending.…”
Section: Introductionmentioning
confidence: 94%
“…Bending is important in the shaping of complex parts, and it is also critical in the joining of outer skins to inner sheet panels by hemming. Appropriate strength levels for automotive aluminum panels are achieved by a combination of alloy composition and thermo mechanical treatment [1,2], and several experimental studies concern the influence of alloy composition on bend performance of Al 6xxx automotive sheet [3][4][5][6]. The bendability has been shown to decrease with increasing copper, iron and Si content.…”
Section: Introductionmentioning
confidence: 99%